High-intensity interval training alleviates ethanol-induced renal damage: A study on inflammation, oxidative stress, and histopathological changes in rats - Najmeh Sadat Hosseini; Sara Shirazpour; Gholamreza Sepehri; Shahriar Dabiri; Manzumeh Shamsi Meymandi (Drug and Alcohol Dependence Reports)
Background: This study examines if high-intensity interval training (HIIT) can reduce ethanol-induced kidney damage by modulating cytokines and reducing oxidative stress. Method: Thirty male Wistar rats were randomly assigned to five groups (n = 6): CON (saline control), ET (ethanol; 3 mg/kg of 20 % ethanol gavage), HIIT (8 weeks of HIIT), HIIT-SL (saline + HIIT), and HIIT-ET (ethanol + HIIT). Kidney tissues were collected for biochemical analysis of cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10); oxidative stress markers, including malondialdehyde (MDA); and antioxidants, including total antioxidant capacity (TAC), glutathione peroxidase (GPx), and superoxide dismutase (SOD). Histopathology and serum levels of albumin, urea, and creatinine were evaluated. Statistical significance was assessed using GraphPad Prism (p < 0.05). Results: Chronic ethanol consumption increased pro-inflammatory cytokines TNF-α and IL-6 (p < 0.0001) and decreased anti-inflammatory IL-10 (p < 0.0001). Histopathology revealed tubular necrosis, and hyaline casts. HIIT reduced TNF-α and IL-6 while increasing IL-10 (p < 0.0001), showing an anti-inflammatory effect. The HIIT-ET group had fewer hyaline casts and less tubular necrosis compared to the ET group, although hyperemia persisted. HIIT improved antioxidant levels (TAC, GPx, SOD) and reduced oxidative stress (MDA) (p < 0.05). Serum urea and creatinine were higher in the ET group but lower in the HIIT-ET group; albumin levels were increased with HIIT. Conclusion: The study shows HIIT effectively reduces ET-induced kidney damage by decreasing oxidative stress and inflammation, suggesting it as a promising non-drug approach to manage ET-related renal issues.